Badanie pochodnych instrumentów finansowych w świetle uregulowań Międzynarodowych Standardów Rewizji Finansowej - Muszyński, Michał (The Derivatives' Audit in the Context of International Standards on Auditing, 2005)
There are new problems connected with a derivatives' audit for auditors. The problems result from the new Polish law regulations in the financial instruments domain. This paper shows sources of the audit's standards and it presents the procedure of the derivatives' audit. Three stages of derivatives' audit have been recognized and characterized: preparing of the derivatives' audit, execution and conclusion of the audit.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 347-357